please tennetiraj86 please answer this I will Mark you brainlist
Attachments:
![](https://hi-static.z-dn.net/files/dd0/42bd5ffccc52809a78a5afe0822322b9.jpg)
Answers
Answered by
0
Answer:
I hope it will help you.
(a^2-a-b)(a^2-a-2)
= (a^2-a-2) . a^2 + (a^2-a-2) (-a) + (a^2-a-2) (-b)
= (a^2-a-2) . a^2 + (a^2-a-2) (-a) + )(a^2-a-2) (-b)
= a^2-a . a^2-2a^2 + (a^2-a-2) (-a) + (a^2-a-2 (-a^2-a-20 (-b)
= a^4-a . a^2-2a^2- (a^2-a-2) . a + (a^2-a-2) 9-b)
= a^4 -a^3-a . a^2 - +a^2 +ba+2a+2b
Answered by
5
Step-by-step explanation:
refer to the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d3b/8c23f8169bef1b39bb7e7e59f184b315.jpg)
Similar questions